BUSINESS AUTOMATION IN THE FIELD OF LIGHT INDUSTRY - V. Zhuravel; A. Shulepova (Вестник Северо-Кавказского федерального университета, 2022)
The article explores pressing issues of production automation in the light industry, distinguishes the distinctive features of its implementation in the field of small business and large enterprises. The goal of scientific research was selected and implemented: to analyze automation options at various stages of production, including the example of light industry enterprises in the Stavropol Territory. The theoretical and methodological basis of the research is made up of scientific works of domestic researchers in the field of light industry, a variety of media and interviewing industry professionals. Arguments are presented conirming the importance of automation of light industry and the need for its implementation in the Stavropol Territory and Russia.